Pembuatan gas methane dari limbah padat penyamakan kulit - Prayitno Prayitno (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1996)
Leather tanning industry is one of the industry which potentially causes environmental problem. For processing, a lot of water and chemical are used, generates a lot of liquid waste, which are powerful pollution in water an in soil. There will also be animal residues from such operation as cleaning, fleshing, splitting and trimming. Each of these generates solid waste which must be disposed. It is a big problem for handling the solid waste because of their volume and highly odours when they decompose in their solid form. Untanned solid waste and liquid waste generated in the tanning process have a high organic content (protein and fats) and their humidity …. are such that they are readily degradated by methane fermentation. ABSTRAK Industri penyamak kulit adalah salah satu industri yang sangat potensial menyebabkan problem lingkungan. Dalam prosesnya diperlukan banyak air dan bahan kimia yang akan menjadi limbah cair yang dapat menyebabkan terjadinya pencemaran air atau masuk dalam tanah. Juga sisa-sisa dari proses pencucian, fleshing, splitting dan trimming akan menghasilkan limbah padat. Untuk menangani limbah padat banyak menimbulkan permasalahan karena volume yang cukup besar dan bau yang ditimbulkan. Limbah tak tersamak dan limbah ciar yang diperoleh dalam proses penyamakan mempunyai kandungan bahan organic yang cukup tinggi (protein dan lemak) dan juga kandungan air yang cukup sehingga memungkinkan untuk didegradasi dengan cara fermentasi methane.